2012
DOI: 10.1097/ccm.0b013e318236efde
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effects of melanocortins on short-term changes in a rat model of traumatic brain injury*

Abstract: Our data indicate that melanocortins protect against traumatic brain injury, in a broad time window and through activation of MC4 receptors, by counteracting the main traumatic brain injury-related mechanisms of damage. These findings could have major clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…NDP-α-MSH, acting through MC4R, modulates inflammatory and apoptotic cascades in a model of global cerebral ischemia in gerbils [17] and activation of MC4R improves survival in a model of severe haemorrhagic shock in rats [18]. Furthermore, NDP-α-MSH protects against traumatic brain injury through MC4R activation [19]. These data support the notion that protective effects of melanocortins in the CNS are mediated mainly by MC4R activation.…”
Section: Introductionsupporting
confidence: 73%
“…NDP-α-MSH, acting through MC4R, modulates inflammatory and apoptotic cascades in a model of global cerebral ischemia in gerbils [17] and activation of MC4R improves survival in a model of severe haemorrhagic shock in rats [18]. Furthermore, NDP-α-MSH protects against traumatic brain injury through MC4R activation [19]. These data support the notion that protective effects of melanocortins in the CNS are mediated mainly by MC4R activation.…”
Section: Introductionsupporting
confidence: 73%
“…38 Substantial neuronal cell damage is observed in the brain especially in the CA3 region of the hippocampus after CHI if the injury is severe enough (for example, 450 g × 2 m). 5,43,60 Our data that acute Cerebrolysin treatment starting 1 hour after CHI significantly decreases neuronal cell loss in the DG and CA3 support a neuroprotective effect of Cerebrolysin. Preclinical studies have shown that acute treatment with Cerebrolysin reduces cerebral infarction in rats after transient ischemia while delayed administration of Cerebrolysin promotes neurological functional recovery without reducing lesion volume.…”
Section: Discussionmentioning
confidence: 49%
“…Other agents have also been shown to mediate IL-10 upregulation and neuroprotection. For example, the endogenous peptides, melanocortins have been shown to induce IL-10 production and reduce tissue damage after cerebral ischemia and traumatic brain injury (Bitto et al, 2012; Spaccapelo et al, 2013). …”
Section: Discussionmentioning
confidence: 99%